Analysis of elementary school students' misconceptions on magnetism using certainty of response index method - Syarivah, Khalimatus; Ngazizah, Nur; Anjarini, Titi (Jurnal Ilmiah Pendidikan Dasar, 2025)
Understanding key scientific concepts is vital for elementary students, yet misconceptions are common. This study identifies misconceptions about magnetism among sixth-grade students at SDN Muhammadiyah Purworejo using the Certainty of Response Index (CRI) method. Involving 33 fourth-grade students, the research employed a qualitative case study approach with CRI-based diagnostic tests. Responses were categorized into four groups: “guessing,” “understanding the concept,” “not understanding the concept,” and “misconceptions.” Results showed the highest misconceptions in how to make a magnet, followed by the magnetic field, understanding magnets, magnetic poles, and distinguishing magnetic from non-magnetic objects, with the lowest misconceptions in the application of magnets in daily life. The study highlights the need for effective teaching strategies to address these misconceptions and improve students' understanding of magnets.